2018
DOI: 10.2147/ijn.s179290
|View full text |Cite|
|
Sign up to set email alerts
|

From 3D spheroids to tumor bearing mice: efficacy and distribution studies of trastuzumab-docetaxel immunoliposome in breast cancer

Abstract: PurposeNanoparticles are of rising interest in cancer research, but in vitro canonical cell monolayer models are not suitable to evaluate their efficacy when prototyping candidates. Here, we developed three-dimensional (3D) spheroid models to test the efficacy of trastuzumab-docetaxel immunoliposomes in breast cancer prior to further testing them in vivo.Materials and methodsImmunoliposomes were synthesized using the standard thin film method and maleimide linker. Two human breast cancer cell lines varying in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Animal tumor model studies were performed in strict accordance with guidelines for animal welfare in experimental oncology and were approved by local ethics committees. Precise description of experimental protocols was reported elsewhere (see [15] for the volume measurements and [25] for the fluorescence measurements).…”
Section: Mice Experimentsmentioning
confidence: 99%
“…Animal tumor model studies were performed in strict accordance with guidelines for animal welfare in experimental oncology and were approved by local ethics committees. Precise description of experimental protocols was reported elsewhere (see [15] for the volume measurements and [25] for the fluorescence measurements).…”
Section: Mice Experimentsmentioning
confidence: 99%
“…The three batches of immunoliposomes were then tested in vitro on bidimensional (2D) and three-dimensional (3D) models. We found that similarly to standard MTT assays 26,34 , apoptosis studies using 2D models were not suitable to discriminate the efficacy of the various immunoliposomes as compared with free docetaxel or liposomal docetaxel. Conversely when using 3D spheroids, we found that all immunoliposomes performed better than free docetaxel and its liposomal form.…”
Section: Discussionmentioning
confidence: 82%
“…In vitro efficacy studies: three-dimensional (3D) model. Empty liposomes and trastuzumab alone did not show cytotoxic effect on MDA-MB-453 (data not shown) 26 . Spheroid monitoring is summarized in Fig.…”
Section: Detection Of Immunoliposomes and Quantification Of Coated Trmentioning
confidence: 88%
See 2 more Smart Citations